Designer umbilical cord-stem cells induce alveolar wall regeneration in pulmonary disease models - Iwatake, Mayumi; Nagamura-Inoue, Tokiko; Doi, Ryoichiro; Tanoue, Yukinori; Ishii, Mitsutoshi; Yukawa, Hiroshi; Matsumoto, Keitaro; Tomoshige, Koichi; Nagayasu, Takeshi; Tsuchiya, Tomoshi (Frontiers in Immunology, 2024)
Background: Researchers are focusing on cellular therapy for chronic obstructive pulmonary disease (COPD) using mesenchymal stem cells (MSCs), with human bone marrow-derived MSCs (hBM-MSCs) leading the way. However, BM-MSCs may not be as optimal as therapeutic cells owing to their low growth potential, invasive harvesting, and high expression of aging-related genes with poor differentiation potential. Consequently, umbilical cord-derived MSCs (hUC-MSCs), which have many excellent features as allogeneic heterologous stem cells, have received considerable attention. Allogeneic and heterologous hUC-MSCs appear to be promising owing to their excellent therapeutic properties. However, MSCs cannot remain in the lungs for long periods after intravenous infusion.Objective: To develop designer hUC-MSCs (dUC-MSCs), which are novel therapeutic cells with modified cell-adhesion properties, to aid COPD treatment.Methods: dUC-MSCs were cultured on type-I collagen gels and laminin 411, which are extracellular matrices. Mouse models of elastase-induced COPD were treated with hUC-MSCs. Biochemical analysis of the lungs of treated and control animals was performed.Results: Increased efficiency of vascular induction was found with dUC-MSCs transplanted into COPD mouse models compared with that observed with transplanted hUC-MSCs cultured on plates. The transplanted dUC-MSCs inhibited apoptosis by downregulating pro-inflammatory cytokine production, enhancing adhesion of the extracellular matrix to alveolar tissue via integrin β1, promoting the polarity of M2 macrophages, and contributing to the repair of collapsed alveolar walls by forming smooth muscle fibers. dUC-MSCs inhibited osteoclastogenesis in COPD-induced osteoporosis. hUC-MSCs are a promising cell source and have many advantages over BM-MSCs and adipose tissue-derived MSCs.We developed novel designer cells that may be involved in anti-inflammatory, homeostatic, injury repair, and disease resistance processes. dUC-MSCs repair and regenerate the alveolar wall by enhancing adhesion to the damaged site. Therefore, they can contribute to the treatment of COPD and systemic diseases such as osteoporosis.